Preliminary Report on Non-adherence to Antihypertensive Treatment in Essential Hypertensive Patients: A Community Based Survey - Ekram, ARM Saifuddin; Hussain, S Monira; Boonshuyar, Chaweenwon (TAJ: Journal of Teachers Association, 2009)
A cross-sectional study was conducted on 300 hypertensive patients living in urban and rural community in Rajshahi District of Bangladesh to assess the situation regarding antihypertensive drug non- adherence. Patients aged 35 years or above who are taking anti-hypertensive drug for at least 6 months were included in the study. About 87% of patients were found non-adherent to treatment. The non-adherent patients had missed taking medication for anywhere from one day to the whole month. The reasons for not taking the medication included forgetfulness (54.1%), busy schedule (13.9.0%), boredom, travel, reluctance to take, and reluctance to buy the medication. Almost 80% of the people know that hypertension is an incurable disease and the disease has no definite sign and symptom. Knowing all these factors why these people are non-adherent to treatment needs further exploration. doi: 10.3329/taj.v21i2.3788 TAJ 2008; 21(2): 112-117